There is variability in the attainment of developmental milestones in the CDKL5 disorder - Fehr, S.; Leonard, H.; Ho, G.; Williams, S.; de Klerk, N.; Forbes, D.; Christodoulou, J.; Downs, Jennepher (BioMed Central Ltd, 2015)
Background: Individuals with the CDKL5 disorder have been described as having severely impaired development. A few individuals have been reported having attained more milestones including walking and running. Our aim was to investigate variation in attainment of developmental milestones and associations with underlying genotype. Methods: Data was sourced from the International CDKL5 Disorder Database, and individuals were included if they had a pathogenic or probably pathogenic CDKL5 mutation and information on early development. Kaplan-Meier time-to-event analyses investigated the occurrence of developmental milestones. Mutations were grouped by their structural/functional consequence, and Cox regression was used to investigate the relationship between genotype and milestone attainment. Results: The study included 109 females and 18 males. By 5 years of age, only 75% of the females had attained independent sitting and 25% independent walking whilst a quarter of the males could sit independently by 1 year 3 months. Only one boy could walk independently. No clear relationship between mutation group and milestone attainment was present, although females with a late truncating mutation attained the most milestones. Conclusion: Attainment of developmental milestones is severely impaired in the CDKL5 disorder, with the majority who did attain skills attaining them at a late age. It appears as though males are more severely impaired than the females. Larger studies are needed to further investigate the role of genotype on clinical variability.